Acidic Environment Effect on the Push-out Bond Strength of Mineral Trioxide Aggregate Mixed with Different Liquids - Ratih, Diatri Nari; Putri, Asri Riany (UI Scholars Hub, 2015)
Mineral trioxide aggregate (MTA) as retrograde filling is always in contact to inflamed tissues in periradicular area. Objective: To investigate the effect of acidic environment on push-out bond strength of MTA mixed with sterile water, local anesthetic, and 5% CaCl2. Methods: Thirty middle third of mandibular premolar roots were randomly assigned into 3 groups of 10 each. MTA mixed with sterile water (Group 1), local anesthetic (group 2), 5% CaCl2 (group 3). Each group was then divided into group A: soaked in synthetic tissue fluid with pH 5, and group B: pH 7.4. Specimens were stored in an incubator with a temperature of 370C for 72 hours, undertaken a push-out test, and observed under a stereo-microscope. Results: A two-way ANOVA showed that acidic environment reduced the push-out bond strength of MTA mixed with either sterile water, local anesthetic or 5% CaCl2 (p <0.05). The predominantly failure was a mixture of adhesive and cohesive type. Conclusion: The acidic environment reduced the push-out bond strength of MTA mixed with either sterile water, local anesthetic or 5% CaCl2. MTA mixed with 5% CaCl2 produced the greatest push-out bond strength, whereas MTA mixed with local anesthetic had the lowest push-out bond strength.